2007
DOI: 10.1002/ppap.200730707
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of Transfer Layer and Wear Debris on Various Counterparts Sliding Against Undoped and Doped DLC Coatings

Abstract: Tribological behaviour of undoped DLC (diamond‐like carbon) and titanium‐doped DLC coatings, referred here as TiC:H, were investigated. Tribological properties of frictional contacts with DLC coating significantly depend on the type of counterpart and generally are conditioned on the processes of abrasive wear, and the oxidation of counterpart and coating, and to smaller extent on the process of coating graphitisation. On the other hand, tribological properties of frictional contacts with TiC:H coating are m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…The Ti atoms from coating would easily react with C and O to form TiC and TiO hard phase, whereafter aggregating to form transfer film, and then, the transfer film would adhere to steel ball (Figure A). It has been certified that the existence of transfer film in sliding interface can effectively decrease friction coefficient and simultaneously protect the underlying coating from further removal . In addition, friction‐induced graphitization is considered as one of the main causes of low friction because of the graphite‐like lamellar structure, which can easily shear between each plane .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Ti atoms from coating would easily react with C and O to form TiC and TiO hard phase, whereafter aggregating to form transfer film, and then, the transfer film would adhere to steel ball (Figure A). It has been certified that the existence of transfer film in sliding interface can effectively decrease friction coefficient and simultaneously protect the underlying coating from further removal . In addition, friction‐induced graphitization is considered as one of the main causes of low friction because of the graphite‐like lamellar structure, which can easily shear between each plane .…”
Section: Resultsmentioning
confidence: 99%
“…It has been certified that the existence of transfer film in sliding interface can effectively decrease friction coefficient and simultaneously protect the underlying coating from further removal. 33,34 In addition, friction-induced graphitization is considered as one of the main causes of low friction because of the graphite-like lamellar structure, which can easily shear between each plane. 27 Therefore, the combined effects of transfer film and graphitization lead to the lowest friction coefficient in steady friction stage when tested under dry friction.…”
Section: Related Mechanism Discussionmentioning
confidence: 99%
“…Some investigations show that this transfer layer is composed mainly of graphite-like materials [1,[3][4][5][6][7]11]; however, other investigations demonstrate that it is composed also of steel oxides when the steel counterpart is used [2,[8][9][10][11]. Significantly fewer investigations in this field that are carried out on tungsten- [12][13][14][15][16] or titanium- [10,16] containing carbon coatings show that transfer layers and wear debris contain graphite-like material and tungsten or titanium oxides respectively. Recent studies [13,15] have shown that for the W-C:H-steel frictional contacts, a tribolayer composed of graphite-like material mixed with tungsten oxides grows at the surface of the steel counterpart.…”
Section: Introductionmentioning
confidence: 91%
“…However, some results show that the friction coefficient of both a-C:H and a-C coatings decreases as the humidity of the environment increases [17]. For the frictional contacts of carbon coatings with steel, a possible unfavorable interaction of carbon with iron through its diffusion into the steel counterpart should be taken into consideration [8][9][10][11]19].…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation